An Overview of Chinese Agricultural and Rural Engagement in Ethiopia - Bräutigam, Deborah; Tang, Xiaoyang (International Food Policy Research Institute, 2012)
The recent expansion of Chinese economic engagement in Africa is often poorly documented and not well understood. This paper is the first in an International Food Policy Research Institute-sponsored effort to better understand Chinese engagement in Africa’s agricultural sector. A clearer picture of Chinese activities in agriculture is important as a foundation for Africans and their development partners to more fruitfully engage with an increasingly important actor. This overview paper explores China’s engagement in rural Ethiopia in historical perspective, focusing on foreign aid, other official engagements, and investment by Chinese firms between 1970 and 2011. We find that Chinese engagement in agriculture and rural development in Ethiopia is longstanding, but at present, Chinese farming investment is far smaller than generally believed. Changes in this engagement reflect the changes in China’s engagement in Africa more generally.